Nghiên cứu lý thuyết hóa học lượng tử về tương tác giữa SiHF3 và *C2H, *CH3, NH3, Cl-, Br- - Trung, Nguyễn Tiến; Hùng, Nguyễn Phi; Huế, Trần Thành (Vietnam Journal of Chemistry, 2012)
Theoretical calculations were performed at the MP2(full)/6-31++G(2d,2p) level. The obtained interaction energies of forming complexes range from -0.17 to -11.22 kcal.mol-1 with ZPE correction. The van der Waals interaction results in strength of three complexes A, B and C, which is proved by making use the Atoms in Molecule (AIM) analysis. Contraction of the Si-H bond lengths due to Pauli repulsive interaction and corresponding increase of their stretching frequencies are observed in these complexes. It means that the blue shift is still found in the complexes possessing van der Waals interaction. Two D, E complexes exhibit the classically red-shifting hydrogen bonds with elongation of the Si-H bonds and decrease of their corresponding stretch frequencies, which are primarily contributed by increase of electron density in the s*(Si-H) orbital.